NETFLIX AND TELKOMSEL BUNDLING: DOES SYMBOLIC VALUE MATTER IN CO-BRANDING - Gede Pamungkas, Ardianta; Suparna, Gede; Yudi Setiawan, Putu; Gusti Agung Ketut Gede Suasana, I (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The Subscription Video on Demand market in Indonesia has seen substantial growth, but Netflix's market share dropped by 10% in Q2 2022, losing about 2 million subscribers. To boost customer purchase intention, Netflix partnered with Telkomsel, a leading telecommunication provider, to offer a bundled package. This study explores the mediating role of brand attitude between symbolic value, perceived benefits, and customer purchase intention for the Netflix-Telkomsel bundle. Using an associative quantitative approach and a sample of 100 respondents, data were analyzed with Partial Least Squares (PLS). The results reveal that symbolic value insignificantly influences purchase intention or brand attitude. However, perceived benefits positively and significantly impact both purchase intention and brand attitude. Brand attitude also positively influences purchase intention and mediates the effect of perceived benefits on purchase intention, but not that of symbolic value. Prospective customers prioritize perceived benefits over symbolic value when deciding to purchase the Netflix-Telkomsel bundle.